Crispy squid product development (Case Study: PT. Cupa-Cupa Snack) Pangandaran Regency - Junianto, Junianto; Veronica, Veronica; Anggraeni, Mella; Musthopa, Andrean Alief (Nekton, 2024)
PT Cupa-Cupa Snack is a company in Pangandaran that processes fishery products into snack products, one of which is crispy squid. The number of crispy squid producers in Indonesia is a challenge for companies to develop products to produce innovations that suit market needs and maintain competitiveness. The purpose of this study was to analyze the product development carried out by the cupa-cupa snack company. The study was conducted from August to October 2024. The research method used was the survey method, with interview techniques and observations of crispy squid products that were analyzed descriptively and qualitatively. The results showed that the company has developed in various aspects, such as the addition of raw material suppliers from various regions, the use of faster and more modern production equipment and processes, changing the formulation of non-msg additives that are safe for consumption, using quality aluminum foil packaging, increasing flavor variants, and business-to-business marketing that maintains good and consistent digital presence techniques on various social media, such as Instagram, Facebook, and TikTok, to increase market share and company competitiveness.